The importance of libraries in enhancing qualitative education in Nigeria (2012)
This paper gave an insightful discourse on the importance of libraries from a general point of view and discusses the various kinds of libraries. It highlighted the qualities of libraries and how they affect the quality of education at the primary, secondary and tertiary levels. It also discussed the reading culture as it affects libraries and quality education at all levels. Quality library personnel and library organization with respect to quality education are among issues raised and addressed in the paper. The paper further discusses new trends in library operations, such as virtual libraries and their implications in ensuring quality education in the information age. It recommended the establishment of standard libraries and suggested ways in which education policy makers and other stakeholders in the educational sector could foster quality education through libraries.